Дело о Джеке - Вытрясателе: повесть / Э. Родда ; пер. с англ. И. Сабинина - Родда Эмили (Черный котенок, 1998)
Экземпляры: Д.О. (20210129) / Инвентарный номер: 33569 / Цена: 16.00 / Сис.шифр: 84(3) / Авт.знак: Р 60 / ГРНТИ: 17.82 / ББК: 84(4Вел)